The Influence of Pdca (Plan, Do, Check, Act) Based on KPI (Key Performance Indicators) on Increasing the Performance of Librarians at Athirah Islamic School Makassar - Amis, Moh; Iskandar, Iskandar; Santalia, Indo; Arsyad, Rahmat (Universitas Muhammadiyah Makassar, 2024)
This research aims to describe the influence of PDCA and KPI on performance, describe performance improvement and identify the influence of KPI-based PDCA in measuring performance improvement of Athirah Islamic School Librarians. The methodology used in this research is a quantitative research method with a descriptive approach with a sample size of 29 people from non-probability sampling using a saturated sample method. The data collection used was questionnaires and documents with a Likert scale which were analyzed using descriptive statistics, multiple regression analysis and performance measurement analysis. and validity, reliability, correlation and hypothesis tests were carried out. Based on the results of inferential statistical analysis processing, it was found that the PDCA variable (X1) has t = 0.382 with a probability (sig-t) of 0.00 < 0.05. The same thing was also found in the KPI variable (X2) with a value of t = 0.515 and a probability (Sig-t) of 0.00 < 0.05. Thus the PDCA and KPI variables have a significant influence on Performance (Y). Apart from that, the Fcount analysis produces a value = 350.228 with a probability (sig-F) of 0.00 < 0.05. This shows that there is a significant simultaneous influence between the PDCA (X1) and KPI (X2) variables on Performance (Y). The management of Athirah Islamic School pays more attention to the implementation of KPI-based PDCA in improving performance and pays more attention to factors that are considered to have an influence on librarian performance, both internal and external factors, and it is recommended for other researchers to explore topics, variables and the development of scientific studies. so that in the future it will provide new studies.